Tāthwir Kurrosāh āt-Tādribāt āl-Iliktruniyāh bii Wāsilāh Wārāqāh āl-‘Amāl āl-Mubāsyiroh li Thullāb ās-Shāf ās-Sābi’ fii Mādrosāh āts-Tsānāwiyāh - Laila Rahimah Harahap; Muhammad Taufiq; Zulfiana Herni; Khairunnisa (Mantiqu Tayr: Journal of Arabic Language, 2024)
Students experience difficulties in understanding the rules of Arabic lessons, this is caused by the lack of supporting teaching materials used by teachers in learning. The aim of the research is to produce a product and to determine the feasibility and effectiveness of using the product in learning Arabic. The method used in this research is the R & D method with the Four D (4D) model, namely Define, Design, Developmnet and Disseminate. Data collection was taken from interviews with teachers in the field of Arabic language studies and several students, observations carried out in the classroom, and tests on student learning outcomes obtained from trials, then documentation. The data analysis technique uses an independent sample t-test with a significance value of <0.05. Product feasibility is obtained from two validators, namely media experts and material experts. The final results of this research are based on a validity test, namely validation by media experts getting results of 85.7% with very feasible criteria, validation by material experts getting results of 95.4% with very feasible criteria. In the assessment of students in the control class and experimental class, the average score was 58.3, increasing to 84.5 in the control class and an average of 34.9, increasing to 90.1 in the experimental class. Thus, it can be stated that the Liveworksheet-based E-LKPD is very feasible and effective for use in Arabic language learning for class VII Madrasah Tsanawiyah students. The scientific contribution of this product is that we hope it can be used in learning activities in the current Independent Curriculum era and for future research, hopefully we can further develop this research.